Progress in methods for evaluating Schwann cell myelination and axonal growth in peripheral nerve regeneration via scaffolds - Ling, Jue; He, Chang; Zhang, Shuxuan; Zhao, Yahong; Zhu, Meifeng; Tang, Xiaoxuan; Li, Qiaoyuan; Xu, Liming; Yang, Yumin (Frontiers in Bioengineering and Biotechnology, 2023)
Peripheral nerve injury (PNI) is a traumatic neurological disorder that is frequently induced by accidents, war, and surgical complications, which is of global significance. The severity of the injury determines the potential for lifelong disability of patients. Artificial nerve scaffolds have been investigated as a powerful tool for promoting optimal regeneration of nerve defects. Over the past few decades, bionic scaffolds have been successfully developed to provide guidance and biological cues to facilitate Schwann cell myelination and orientated axonal growth. Numerous assessment techniques have been employed to investigate the therapeutic efficacy of nerve scaffolds in promoting the growth of Schwann cells and axons upon the bioactivities of distinct scaffolds, which have encouraged a greater understanding of the biological mechanisms involved in peripheral nerve development and regeneration. However, it is still difficult to compare the results from different labs, due to the diversity of protocols and the availability of innovative technologies when evaluating the effectiveness of novel artificial scaffolds. Meanwhile, due to the complicated process of peripheral nerve regeneration, several evaluation methods are usually combined in studies on peripheral nerve repair. Herein, we have provided an overview on the evaluation methods used to study the outcomes of scaffolds based therapies for PNI in experimental animal models, and specially focus on Schwann cell functions and axonal growth within the regenerated nerve.